Analisis Tingkat Kesejahteraan Masyarakat di Provinsi Nusa Tenggara Barat Menggunakan Model Regresi Multivariat - Syam, Rahmat; Sukarna, Sukarna; Nurmah, Nurmah (Journal of Mathematics, Computations and Statistics, 2020)
This study aims to determine the model of the relationship between the rate of economic growth, the level of Gross Domestic Product Regional each capita, and the Human Development Index for supporting variables base on multivariate regression analysis to analyze the level of public welfare in West Nusa Tenggara Province by selecting the best model using the KICC method. The supporting variables were life expectancy, unemployment rate, expenditure each capita, poverty level, and local income. The data was published by the Central Bureau of Statistics of West Nusa Tenggara Province on 2018. The result shows that there are three variables which have shown a positive impact on the public welfare in West Nusa Tenggara Province, namely life expectancy, expenditure each capita, and local income. However, the others have shown a negative impact. The relation between predictors and response simultaneously is = 0.999990324, it means that the data is explainable 99.99% by the model.